2006
DOI: 10.1063/1.2180728
|View full text |Cite
|
Sign up to set email alerts
|

Experimental test of the neoclassical theory of impurity poloidal rotation in tokamaks

Abstract: Despite the importance of rotation in fusion plasmas, our present understanding of momentum transport is inadequate. The lack of understanding is in part related to the difficulty of performing accurate rotation measurements, especially for poloidal rotation. Recently, measurements of poloidal rotation for impurity ions (Z>1) have been obtained in the core of DIII-D [J. L. Luxon, Nucl. Fusion 42, 6114 (2002)] plasmas using charge exchange recombination spectroscopy. The inferred poloidal rotation is bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
121
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(132 citation statements)
references
References 32 publications
(18 reference statements)
9
121
2
Order By: Relevance
“…[5][6][7] Furthermore, recent experiments at DIII-D indicate that deviations in the magnitude as well as direction of the poloidal rotation of impurity ions from that predicted by neoclassical theory can be present throughout the plasma volume. 8 Within the above studies, measured poloidal flows have been observed to deviate from neoclassical predictions by as much as an order of magnitude. These substantial deviations of poloidal flows from neoclassical predictions are suggestive of the critical role in which turbulent stresses are likely playing in the generation of mean poloidal flows.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Furthermore, recent experiments at DIII-D indicate that deviations in the magnitude as well as direction of the poloidal rotation of impurity ions from that predicted by neoclassical theory can be present throughout the plasma volume. 8 Within the above studies, measured poloidal flows have been observed to deviate from neoclassical predictions by as much as an order of magnitude. These substantial deviations of poloidal flows from neoclassical predictions are suggestive of the critical role in which turbulent stresses are likely playing in the generation of mean poloidal flows.…”
Section: Introductionmentioning
confidence: 99%
“…While we use this basic picture to justify using the parallel Reynolds stress to represent the toroidal one, it should be noted that there are recent indications that poloidal rotation may also be anomalous 40,41 or at least radially varying deviations from an average neoclassical poloidal rotation should be expected. 42 The remainder of this paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, aside from strong core transport barriers, the neoclassical prediction of impurity poloidal rotation is quite small and near the resolution level of the diagnostic designed for the measurement. Early accounts of poloidal rotation contained zero within the error bars of the measurements [21], but through sophisticated atomic calculations [22,23] and novel diagnostic viewing configurations [24,25,26] the measurements uncertainties have been reduced to such levels that the poloidal flow theory may be tested.…”
Section: Introductionmentioning
confidence: 99%